2008
DOI: 10.1130/ges00143.1
|View full text |Cite
|
Sign up to set email alerts
|

Structural and stratigraphic evolution of the Calico Mountains: Implications for early Miocene extension and Neogene transpression in the central Mojave Desert, California

Abstract: New geologic mapping, structural data, and 40 Ar/ 39 Ar geochronology document early Miocene sedimentation and volcanism and Neogene deformation in the Calico Mountains, located in a complexly deformed region of California's central Mojave Desert. Across most of the Calico Mountains, volcaniclastic sediments and dacitic rocks of the Pickhandle Formation accumulated rapidly between ca. 19.4 and 19 Ma. Overlying fi ne-grained lacustrine beds (here referred to as the Calico Member of the Barstow Formation) are br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…1 and 2;McCulloh, 1952;Dibblee, 1994;Fillmore and Walker, 1996). Previous radiometric dating of the Pickhandle Formation indicates an early Miocene age, bracketed between 23.7 and 18.9 Ma (Burke et al, 1982;Walker et al, 1995;Fillmore and Walker, 1996); additional 40 Ar/ 39 Ar ages by Singleton and Gans (2008) in the southeastern Calico Mountains suggest that the age of volcanic and intrusive rocks of the Pickhandle Formation in this area is 19.3-19.0 Ma. Due to its coarse-grained nature and outcrop proximity to the CMMCC, previous studies suggested that the Pickhandle Formation-and possibly the Jackhammer Formation-represent synextensional supradetachment-basin deposits (Fillmore et al, 1994;Fillmore and Walker, 1996).…”
Section: Stratigraphic Framework Of the Central Mojave Desertmentioning
confidence: 91%
See 3 more Smart Citations
“…1 and 2;McCulloh, 1952;Dibblee, 1994;Fillmore and Walker, 1996). Previous radiometric dating of the Pickhandle Formation indicates an early Miocene age, bracketed between 23.7 and 18.9 Ma (Burke et al, 1982;Walker et al, 1995;Fillmore and Walker, 1996); additional 40 Ar/ 39 Ar ages by Singleton and Gans (2008) in the southeastern Calico Mountains suggest that the age of volcanic and intrusive rocks of the Pickhandle Formation in this area is 19.3-19.0 Ma. Due to its coarse-grained nature and outcrop proximity to the CMMCC, previous studies suggested that the Pickhandle Formation-and possibly the Jackhammer Formation-represent synextensional supradetachment-basin deposits (Fillmore et al, 1994;Fillmore and Walker, 1996).…”
Section: Stratigraphic Framework Of the Central Mojave Desertmentioning
confidence: 91%
“…1 and 2; Glazner et al, 2002). East-west-trending folds are also observed within the central Mojave Desert, with crustal shortening attributed to local transpression related to northwest-trending right-lateral faults (e.g., Dibblee, 1980;Singleton and Gans, 2008) or regional north-south compression (Bartley et al, 1990). In the Calico Mountains, the main geologic structure is the northwest-trending Calico fault (Figs.…”
Section: Research Papermentioning
confidence: 94%
See 2 more Smart Citations
“…Generalized geologic map of the central Mojave Desert region near the Calico Mountains, showing the location of the Waterman Hills detachment fault (WHDF) and the distribution of early Miocene rocks in the area (modi ed fromSingleton and Gans, 2008…”
mentioning
confidence: 99%